Combination of adaptive and intelligent load shedding techniques for distribution network - Karimi, M.; Mokhlis, Hazlie; Bakar, A.H.A.; Laghari, J.A.; Shahriari, A.; Aman, M.M. (2012)
One of the challenge in islanding operation is to maintain frequency stability when generation is less than demand. This paper presents a new Under-Frequency Load shedding scheme for an islanded distribution network. The scheme is based on an adaptive and intelligent load shedding techniques. This proposed scheme is able to conserve power system collapse even for large disturbance and events in the system. The proposed scheme is evaluated through simulation in PSCAD/EMTDC software. A distribution network connected with mini-hydro generation in Malaysia is chosen for the test. Various test scenarios show the effectiveness of the proposed load shedding scheme to shed optimum load.